Pengaruh lama ekstraksi dan fermentasi dalam pembuatan minyak kelapa terhadap rendemen dan sifat sensoris minyak kelapa - Khumairoh Asy Syifa; Karseno Karseno; Pepita Haryanti (AGROINTEK, 2025)
Coconut oil is a processed product from old coconut meat in the form of aClear-colored liquid with a distinctive coconut smell. This research aimed to determine the effect of extraction time and concentration (mixer) and fermentation (tempeh yeast) time on the highest yield of coconut oil and sensory properties by using extraction and fermentation time. There were three treatments in this study, namely extraction time P1= 5 minutes. P2= 10 minutes. P3= 15 minutes and tempeh yeast concentration R1= 1%. R2=3% and R3=5% with three repetitions. The analysis yielded data using ANOVA, which was further tested with Duncan, and sensory testing was conducted with Friedman. The observation parameters include the highest yield of coconut oil and the sensory properties of coconut oil in accordance with SNI. From these three treatments, the highest yield combination, P3R1, was obtained with an extraction time of 15 minutes and a tempeh yeast concentration of 1%. The highest yield of coconut oil was 17.76%. The sensory quality of the obtained is that the color of the coconut oil is clear, and slightly yellowish, the fragrance of the coconut oil has a typical coconut, and the panelists like it.